Design and Development of an Integrated Web-based System for Tropical Rainfall Monitoring - Trono, Edgar Marko (Archīum Ateneo, 2014)
This study is about the design and development of an integrated web-based system for tropical rainfall monitoring. The system gathers data using a network of low-cost, Android-based acoustic rainfall sensors, a nationwide infrastructure of 5 GHz wireless broadband links, and remote weather stations. The low-cost Android-based acoustic rainfall sensors are deployed at high densities over a local area and the 5 GHz wireless broadband sensors gather rainfall information on a nationwide scale. The sensor network provides information about spatial-variations that are characteristics of tropical rain rates, and complement data from the scarcely deployed remote weather stations. Gathered data is then processed and displayed on a web interface.